The art and craft of scientific writing and critical appraisal of a research paper - Ghimire, Bikal (Journal of Society of Anesthesiologists of Nepal, 2017)
Writing is an art and like any art form, it needs perseverance, dedication and practice. However, to write a good quality paper, the habit of reading scientific articles and analyzing them is very important. With the advent of internet and online publishing, we have access to colossal research articles on myriads of subjects making extraordinary conclusions.  Evidence based practice requires us to rely on literature for our clinical practice, and we have abundant publications on all aspects claiming to justify all sides of the argument. In this context it becomes more important for all in clinical practice to be able to dissect an article and analyze it in details.